Algorithm 762 LLDRLF, log-likelihood and some derivatives for log-F models. - Brown, Barry W. (ACM transactions on mathematical software.)
The flexible statistical models incorporating the log-F distribution are little used because of numeric difficulties. We describe a method for calculating the log-likelihood and two derivatives with respect to the data argument. Fortran subroutines incorporating these calculations are provided.